Psychological Motives for Crying in Umayyad Love Poetry - Jaddi, Enas Khader; Saloum, Enaam Daoud (Journal of Ecohumanism, 2024)
The psychological structure interacts between its internal components at the moment of the occurrence of the event that stimulates the emergence of that structure, and then the self composed of the psychological structure, customs, traditions and legacies is in another conflict, and from those internal conflicts comes crying, representing the process of deprivation of desire, and desire in its various forms, so that tears, crying, regret and pain are the result of the entire process, as a result of the relationship between the poet and his beloved, and the various influences that revolve around them.